The Predictive Value of Optimism in Psychological Flow: A Comparatives Study Among Faculty Members (Gulf States and Egypt) - Elsherbi, Atef; Al Attiyah, Asma (Jordan Journal of Educational Sciences, 2019)
The study aimed at identifying the relationship between the psychological flow and optimism among faculty members (Gulf States and Egypt), and identifying the predictive value of optimism in psychological flow. The sample of the study consisted of (124) faculty members from different universities in the Gulf and Egypt as follows: (20) Saudis, (19) Omanis, (40) Qataris and (45) Egyptians. The tools of the study included psychological flow scale (prepared by the researchers) and an optimism scale (Abdel-Khalek, 1996). The results of the study showed statistical significant differences in mean scores of faculty members in the Gulf and Egypt on the psychological flow scale, in favor of the Gulf States. The results also show statistical significant differences in mean scores of faculty members in the Gulf and Egypt on the optimism scale, in favor of the Gulf States. Finally, optimism was found to be predictive of psychological flow among faculty members.